2013
DOI: 10.1089/pop.2012.0048
|View full text |Cite
|
Sign up to set email alerts
|

Improving Patient Experience by Transforming Primary Care: Evidence from Geisinger's Patient-Centered Medical Homes

Abstract: Patient-centered medical homes (PCMHs) have the potential to improve patient experience of care. Since 2006, Geisinger Health System has implemented its own version of an advanced PCMH model, referred to as ProvenHealth Navigator (PHN). To evaluate the impact of PHN on patient experience of care, the authors conducted a survey of patients whose primary care clinics had been transformed to "PHN sites" and were under case management at the time of the survey. A comparable survey of patients from non-PHN sites al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 10 publications
2
86
1
Order By: Relevance
“…Subsequently, all our medical providers and senior staff, including physicians, physician assistants or nurse practitioners, nurses, and medical assistants have now been required to complete courses on communication specific to health literacy as well as motivational interviewing to promote self-management and health behavior change. Contrary to a study of Geisinger PCMHs that patients seem to be somehow content with their access to care [19], however, our survey findings indicated that our patients want more access to their providers.…”
Section: Discussioncontrasting
confidence: 99%
“…Subsequently, all our medical providers and senior staff, including physicians, physician assistants or nurse practitioners, nurses, and medical assistants have now been required to complete courses on communication specific to health literacy as well as motivational interviewing to promote self-management and health behavior change. Contrary to a study of Geisinger PCMHs that patients seem to be somehow content with their access to care [19], however, our survey findings indicated that our patients want more access to their providers.…”
Section: Discussioncontrasting
confidence: 99%
“…47 Our study fills an important gap in the literature because existing demonstration-project evaluation efforts have focused on system-level cost savings (eg, through fewer emergency department or specialty visits), which have been inconsistently observed. 10,[14][15][16]18,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] For many practices, revenue gains must be observed at the practice level to justify practice-level workforce and time use changes. Another key advantage is that our modeling allows us to compare different reforms in the same practices, unlike demonstration projects for which it is unclear whether differences in outcomes are due to differences in the PCMH funding program itself or preexisting practice differences.…”
Section: Discussionmentioning
confidence: 99%
“…4,[57][58][59] On the other hand, early innovations and primary care transformation projects have demonstrated successful ways to improve primary care effectiveness and efficiency and, if done well, to return joy to practice. [60][61][62][63] This convergence of concern and opportunity has produced the key questions that drove the evolution of Family Medicine for America's Health: • Core attributes: What are the core attributes of family medicine today-and what do they need to be in the future-for our profession to achieve the Triple Aim in the service of our patients in the context of the larger health care landscape? …”
Section: Historical Context: the Future Of Family Medicine Projectmentioning
confidence: 99%